Public sector audit recommendations: a systematic literature review based on scopus and google scholar - Hari Haryanto; Teguh Kurniawan; Roy Valiant Salomo (Lentera Negeri, 2026)
This study conducts a Systematic Literature Review (SLR) on public sector audit recommendations using the PRISMA framework. From an initial pool of approximately 730 articles, a total of 60 articles (30 Scopus and 30 Google Scholar) published between 2000 and 2025 were selected based on predefined criteria. However, no formal quality appraisal was conducted; thus, the findings reflect aggregated evidence rather than weighted conclusions. Thematic analysis identifies five dominant themes: follow-up effectiveness, determinants of implementation, corruption prevention, the role of Supreme Audit Institutions (SAIs), and performance auditing. These themes emerged from recurring patterns across studies. The findings indicate that audit recommendation follow-up is predominantly associated with improvements in financial reporting quality and public accountability, although some studies report null or context-dependent results. Institutional factors particularly leadership commitment, auditor competence, and audit independence are key determinants. While international and Indonesian studies show broadly similar patterns, the dominance of Indonesian evidence limits generalizability. This review provides a structured synthesis but should be interpreted as indicative rather than causal.